2016
DOI: 10.4271/2016-01-0824
|View full text |Cite
|
Sign up to set email alerts
|

Cycle-by-Cycle Analysis of Cold Crank-Start in a GDI Engine

Abstract: The first 3 cycles in the cold crank-start process at 20°C are studied in a GDI engine. The focus is on the dependence of the HC and PM/PN emissions of each cycle on the injection strategy and combustion phasing of the current and previous cycles. The PM/PN emissions per cycle decrease by more than an order of magnitude as the crank-start progresses from the 1 st to the 3 rd cycle, while the HC emissions stay relatively constant. The wall heat transfer, as controlled by the combustion phasing, during the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The issue becomes more pronounced under cold-start conditions when multiple injection strategies are implemented. 8,9 The variations in the local properties at the spark plug locations play a significant role in the growth of the initial kernel established by the spark, and its subsequent evolution into a turbulent flame. To accurately model the DISI combustion process, it is important to account for the effects of the spark ignition process.…”
Section: Introductionmentioning
confidence: 99%
“…The issue becomes more pronounced under cold-start conditions when multiple injection strategies are implemented. 8,9 The variations in the local properties at the spark plug locations play a significant role in the growth of the initial kernel established by the spark, and its subsequent evolution into a turbulent flame. To accurately model the DISI combustion process, it is important to account for the effects of the spark ignition process.…”
Section: Introductionmentioning
confidence: 99%
“…4 Within this cold-start phase, the early engine crank-start followed by approximately 20 seconds of the cold-start, fast-idle (catalyst heating) phase is responsible for the major share of emissions. 5,6 To address the cold-start emissions issue, many engines use a split injection strategy, where the first injection takes place during the intake, while the second injection takes place during the compression stroke. It was shown that for a delayed ignition time, this strategy can generate stratified local enrichment around the spark plug, and can, therefore, improve the combustion stability and reduce emissions compared to the single injection strategy.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel mundial se emiten leyes para regular la cantidad de contaminantes emitidos por los motores de combustión a la atmósfera, razón por la cual los fabricantes han desarrollado nuevas tecnologías como vehículos híbridos y eléctricos, pero debido a que este tipo de tecnología todavía no satisface completamente las expectativas de los consumidores, se han visto en la necesidad de desarrollar nuevas tecnologías usando combustibles fósiles, como la inyección directa a gasolina, con el objetivo de cumplir estas normas. Esta tecnología se comercializa en todo el mundo e introduce nuevos conceptos y elementos, además de rediseñar el funcionamiento de algunos elementos ya utilizados en los sistemas tradicionales de inyección indirecta a gasolina los cuales se manifiestan con respecto al ingreso de aire, el suministro de combustible, el salto de chispa y la emisión de gases contaminantes (Rodríguez and Cheng, 2016); (C. Huang et al, 2016). Pero la variación del funcionamiento de los distintos elementos depende del modo de trabajo seleccionado por el módulo de control electrónico, por esto la importancia de conocer la selección del modo de trabajo ya que no hay ningún indicador o parámetro de identificación en la línea de datos que indique el modo de trabajo que se está ejecutando.…”
Section: Introductionunclassified